Oregano essential oil modulates colonic homeostasis and intestinal barrier function in fattening bulls - Ma, Yue; Shi, Jinping; Jia, Li; He, Pengjia; Wang, Ying; Zhang, Xiao; Huang, Yongliang; Cheng, Qiang; Zhang, Zhao; Dai, Youchao; Xu, Meiling; Lei, Zhaomin (Frontiers in Microbiology, 2023)
Oregano essential oil (OEO) primarily contains phenolic compounds and can serve as a dietary supplement for fattening bulls. However, the precise molecular mechanism underlying this phenomenon remains largely elusive. Therefore, this study investigated the impact of adding OEO to diet on the integrity of the intestinal barrier, composition of the colonic microbiome, and production of microbial metabolites in fattening bulls.Our goal was to provide insights into the utilization of plant essential oil products in promoting gastrointestinal health and welfare in animals. We employed amplicon sequencing and metabolome sequencing techniques to investigate how dietary supplementation with OEO impacted the intestinal barrier function in bulls. The inclusion of OEO in the diet resulted in several notable effects on the colon of fattening bulls. These effects included an increase in the muscle thickness of the colon, goblet cell number, short-chain fatty acid concentrations, digestive enzyme activity, relative mRNA expression of intestinal barrier-related genes, and relative expression of the antiinflammatory factor IL-10. Additionally, α-amylase activity and the relative mRNA expression of proinflammatory cytokines decreased. Moreover, dietary OEO supplementation increased the abundance of intestinal Bacteroides, Coprobacillus, Lachnospiraceae_UCG_001, and Faecalitalea. Metabolomic analysis indicated that OEO primarily increased the levels of 5-aminovaleric acid, 3-methoxysalicylic acid, and creatinine. In contrast, the levels of maltose, lactulose, lactose, and D-trehalose decreased. Correlation analysis showed that altered colonic microbes and metabolites affected intestinal barrier function. Taken together, these results demonstrate that OEO facilitates internal intestinal environmental homeostasis by promoting the growth of beneficial bacteria while inhibiting harmful ones.